Traduction automatique des mots sémantiquement proches dans l’approche orientée objets - Śmigielska, Beata (Neophilologica, 2015)
The paper refers to the specifics of the French-Polish automated translation. The author summarizes briefly the rules of creating electronic lexical databases in the context of the Object Oriented Approach. This particular approach, created for the purpose of translation, especially for automated translation, by Wiesław Banyś, offers a specific approach towards the language description with the help of object classes seen through their semantic relations. The purpose of this description is to determine correctly the meaning of the words and polysemic expressions of the source language in the translation into the target language. Therefore, the main question of the paper concerns the role of frames and/or scripts criterion in the process of the natural language words’ disambiguation for automated translation. By analysing the example of the French word collier the Author shows how it is possible to solve the problem of near synonyms in automated translation with the use of the above-mentioned criterion.